Mutations in TMEM76* cause mucopolysaccharidosis IIIC (Sanfilippo C syndrome) - Hrebícek, Martin; Mrázová, Lenka; Seyrantepe, Volkan; Durand, Stéphanie; Roslin, Nicole M; Nosková, Lenka; Hartmannová, Hana; Ivánek, Robert; Cízkova, Alena; Poupetová, Helena; Sikora, Jakub; Urinovská, Jana; et al. (American journal of human genetics, 2006)
Mucopolysaccharidosis IIIC (MPS IIIC, or Sanfilippo C syndrome) is a lysosomal storage disorder caused by the inherited deficiency of the lysosomal membrane enzyme acetyl-coenzyme A: alpha -glucosaminide N-acetyltransferase (N-acetyltransferase), which leads to impaired degradation of heparan sulfate. We report the narrowing of the candidate region to a 2.6-cM interval between D8S1051 and D8S1831 and the identification of the transmembrane protein 76 gene (TMEM76), which encodes a 73-kDa protein with predicted multiple transmembrane domains and glycosylation sites, as the gene that causes MPS IIIC when it is mutated. Four nonsense mutations, 3 frameshift mutations due to deletions or a duplication, 6 splice-site mutations, and 14 missense mutations were identified among 30 probands with MPS IIIC. Functional expression of human TMEM76 and the mouse ortholog demonstrates that it is the gene that encodes the lysosomal N-acetyltransferase and suggests that this enzyme belongs to a new structural class of proteins that transport the activated acetyl residues across the cell membrane.
Keywords: mutace; Animals; Base Sequence; Female; buněčné linie; sekvenční homologie aminokyselin; polymerázová řetězová reakce; Sequence Homology, Amino Acid; Pedigree; Polymerase Chain Reaction; ženské pohlaví; mapování chromozomů; mutační analýza DNA; sekvence aminokyselin; Recombinant Fusion Proteins; rodokmen; lidské chromozomy, pár 8; Chromosome Mapping; transfekce; Transfection; rekombinantní fúzní proteiny; lidé; Molecular Sequence Data; mukopolysacharidóza III; Mice; DNA Mutational Analysis; Mutation; komplementární DNA; Amino Acid Sequence; myši; Cell Line; molekulární sekvence - údaje; acetyltransferasy; Male; Acetyltransferases; Cloning, Molecular; Exons; Mucopolysaccharidosis III; sekvence nukleotidů; Chromosomes, Human, Pair 8; exprese genu; exony; klonování DNA; DNA, Complementary; zvířata; mužské pohlaví; Gene Expression; Humans